Implementation of a Low-Carbohydrate Diet Improves the Quality of Life of Cancer Patients – An Online Survey - Tulipan, Julia; Kofler, Barbara (Frontiers in Nutrition, 2021)
Low Carb (LC) and ketogenic diets (KD) have gained in popularity in recent years. Numerous preclinical studies have studied the effect of KDs on cancer growth, but larger clinical studies in human cancer patients are needed. The current evidence, predominantly in the form of anecdotes and case reports, suggests that KDs could be effective as an adjunct to traditional cancer therapy. However, metabolic therapy options such as the KD are not yet part of the standard of care in cancer patients. Nonetheless, a substantial number of cancer patients have resorted to implementing a KD or LC diet on their own. The aim of the present study was to gather information, via an online questionnaire, to address how cancer patients are implementing KDs and LC diets, whether they perceive any benefits of the diet on quality of life (QoL), and what factors influence feasibility and adherence to the diet. Study participants were asked to fill out an online questionnaire. More than two-thirds of the respondents stated that a LC or KD improved QoL and that it had a normalizing effect on body weight. There was an obvious gap between the patients’ need for professional counseling and what is currently offered in the health care setting. In the future, efforts should be made to invest in nutrition experts who are trained in the KD to support cancer patients in KD implementation.